Mendorong Kemandirian Ekonomi Santri melalui Entrepreneurship pada Pondok Pesantren Mamba'ul Ulum di Mojokerto - Aditya Surya Nanda; Fitryani Fitryani (Ecopreneur : Journal of Sharia Economics Study Program, 2024)
The Mamba'ul Ulum Mojosari Islamic Boarding School is one of the economically independent Islamic boarding schools. This Islamic boarding school offers a number of high quality products that have extraordinary potential if marketed well. Apart from that, the concept of practice a business in the era of digital is also very important, as initial capital for today's successful startups. The goal to be achieved is how the school (in the Islamic boarding school environment) connects and absorbs entrepreneurship teachings and contributes to economic development in the Islamic boarding school environment, by producing products produced by the students. by Mamba'ul Ulum. then it will be sold on e-commerce. This study used descriptive qualitative method. The results of the research provide an illustration of how the principles created as a basis for santri entrepreneurship are useful in improving the economy in the Islamic boarding school environment with the aim of developing the independent economic stability of santri. environment, increasing knowledge and understanding of business potential. The results obtained during the production of products are intended for marketing. Simple use of online marketing tools. Support is provided by subject teachers to maintain stable abilities and understanding. Keywords: Economic Independence, Santri, Islamic Boarding School, Entrepreneur Abstrak Pondok Pesantren Mamba'ul Ulum Mojosari merupakan salah satu pondok pesantren yang mandiri secara ekonomi. Pondok pesantren ini menawarkan sejumlah produk berkualitas tinggi yang memiliki potensi luar biasa jika dipasarkan dengan baik. Selain itu, konsep melatih bisnis di era transformasi digital juga sangat penting, sebagai modal awal bagi santri untuk sukses. Tujuan yang ingin dicapai adalah bagaimana pihak sekolah (di lingkungan pesantren) menghubungkan dan menyerap ajaran-ajaran kewirausahaan serta memberikan kontribusi terhadap pengembangan ekonomi di lingkungan pesantren, dengan menghasilkan produk-produk yang dihasilkan oleh santri Mamba'ul Ulum. Penelitian ini menggunakan metode deskriptif kualitatif. Hasil penelitian memberikan gambaran bagaimana prinsip-prinsip yang diciptakan sebagai landasan kewirausahaan santri bermanfaat dalam meningkatkan perekonomian di lingkungan pesantren dengan mengembangkan kemandirian kemapanan ekonomi santri. lingkungan pondok mampu meningkatkan pengetahuan dan pemahaman tentang potensi bisnis. Hasil yang diperoleh selama produksi produk dimaksudkan untuk dipasarkan. Penggunaan sederhana sarana pemasaran online. Dukungan diberikan oleh guru mata pelajaran untuk menjaga kestabilan kemampuan dan pemahaman. Kata Kunci: Kemandirian Ekonomi, Santri, Pondok Pesantren, Entrepreur